Exploring class identity and inequality in the Department of Human Settlement’s comprehensive housing plan : a case study of Lethuli Park in Polokwane, Limpopo Province, South Africa - Thebe, Vusilizwe (University of Pretoria, 2022)
Dissertation (MSocSci (Development Studies))--University of Pretoria, 2022.